USING STEM EDUCATION FOR PROFESSIONAL DEVELOPMENT AS A VOCATIONAL COLLEGE TEACHER (Innovative professional education, 2023)
The article reveals the aspects of professional growth on the example of a teacher of the Hrytsivskyi VPU - 38 of the Khmelnytsky region, his self-realization in the conditions of socio-economic changes. The importance of STEM education in the activation of the motivational activity of the teacher - student of education based on the professional direction of the subject is determined. The role of interdisciplinary lessons and interdisciplinary tasks for the formation of STEM competence of future specialists is revealed.
Keywords: professional development, professional direction of the subject, interdisciplinary integration